2017
DOI: 10.1007/s11920-017-0823-5
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Stress and Accelerated Cellular Aging: From Epigenetics to Cardiometabolic Disease

Abstract: Purpose of review The aim of this paper is to review the recent literature on traumatic stress-related accelerated aging, including a focus on cellular mechanisms and biomarkers of cellular aging and on the clinical manifestations of accelerated biological aging. Recent findings Multiple lines of research converge to suggest that PTSD is associated with accelerated aging in the epigenome, and the immune and inflammation systems, and this may be reflected in premature onset of cardiometabolic and cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 105 publications
(124 reference statements)
2
46
1
Order By: Relevance
“…We observed increases in Hannum and Horvath age acceleration associated with anxiety, PTSD and low income that were generally of greater size than for mAA (although with wider confidence intervals due to the smaller sample size). Meta‐analyses have shown that both PTSD (Wolf & Morrison, 2017) and low socio‐economic position (Fiorito et al, 2017) are associated with higher Hannum age acceleration. We did not observe any evidence for an association between depression and Hannum or Horvath age acceleration, suggesting epigenetic and metabolomic aging measures may be sensitive to separate dimensions of mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed increases in Hannum and Horvath age acceleration associated with anxiety, PTSD and low income that were generally of greater size than for mAA (although with wider confidence intervals due to the smaller sample size). Meta‐analyses have shown that both PTSD (Wolf & Morrison, 2017) and low socio‐economic position (Fiorito et al, 2017) are associated with higher Hannum age acceleration. We did not observe any evidence for an association between depression and Hannum or Horvath age acceleration, suggesting epigenetic and metabolomic aging measures may be sensitive to separate dimensions of mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Aging has been defined as the “time‐dependent decline of functional capacity and stress resistance, associated with increased risk of morbidity and mortality” (Burkle et al, 2015). Environmental stressors, including lifestyle and social adversity (Stringhini et al, 2018), psychological disorders (Chiu et al, 2018; Wolf & Morrison, 2017), and genetic factors (McDaid et al, 2017) may influence the aging process, leading to differing aging rates. Traditionally, quantitative assessment of “the rate of aging” relies on the analysis of mortality curves of populations.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, systemic inflammation may underlie the pathophysiology of PTSD, as well as the consistent link between PTSD and chronic medical conditions associated with aging, such as cardiovascular, metabolic, autoimmune, and neurodegenerative diseases [4][5][6][7][8], and other markers of accelerated aging [6,7,[9][10][11][12][13][14]. This dysregulated inflammatory state is itself partially coordinated by maladaptive alterations of hypothalamic-pituitary adrenal (HPA) axis activity and sympathetic nervous system (SNS) sensitivity/responsivity [15,16], which affect both peripheral immune cells in blood and neuroimmune dynamics in brain.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD poses a considerable public health concern because of the debilitating nature of the symptoms and because of the high rates of comorbidity with other psychiatric disorders such as major depression and bipolar disorder [10]. People with PTSD also experience chronic inflammation [11••], metabolic disorder [12], increased incidence of coronary artery disease [13, 14], and increased rates of early mortality [8, 15]. …”
Section: Introductionmentioning
confidence: 99%